The role of institutional environments in cross-border mergers : a perspective from bidders’ earnings management behavior - Baik, Bok (2015)
This study examines the effects of targets’ institutional environments on bidders’ earning management behavior around cross-border mergers. Earnings management is a widely used strategy for the bidder to reduce the risk of overpayment and the related costs in mergers. We hypothesize that the extent to which the bidder engages in earnings management differs across the level of uncertainty resulting from the target’s institutional environments such as language, culture, religion, the quality of accounting standards, and political and legal environments. Consistent with our hypothesis, we find that the earnings management behavior of US bidders becomes more evident when they acquire targets from countries with greater institutional differences, such as non-Christian countries, countries with a low level of political stability, countries with a low level of democracy and freedom of the press and media, countries with high corruption and countries with a low level of government effectiveness. Overall, these results suggest that the bidder engages in earnings management to reduce the risk of overpayment arising from uncertainty caused by institutional differences.